Analysis of Accounting Software Utilization Among MSMEs in the Special Region of Yogyakarta Using TAM - Nilna iffa Afifatia Fasya; Helmi Aulia Rachmman (Universitas Mercu Buana Yogyakarta, 2026)
Among 38 provinces in Indonesia, Yogyakarta is the only one with special status. It’s economic growth is supported by two main sectors: education and tourism. The former was selected as the research object as it is related to its function as a benchmark of human resource in Indonesia. Human resource quality also influences micro enterprises that adopts accounting software. In order to measure the influence, Theory of Acceptance Model (TAM) was used. Therefore, this study aims to identify the influence of perceived usefulness, perceived ease of use, and attitude toward using on the behavioral intention to use accounting software among MSMEs in Yogyakarta. The sample were selected via non-random sampling with purposive sampling technique. Data was harvested using Google Forms that has been checked for validity and reliability. Following the classical assumption test and hypothesis testing, this study confirms that perceived usefulness and attitude toward using influence behavioral intention to use, while perceived ease of use has no effect.